AB0695 Predictive factors of long-term clinical outcome in behcet's syndrome patients with ocular involvement: does actually the disease tend to grow dim over time?. (12th June 2018) - Talarico, R.; Figus, M.; Posarelli, C.; d'Ascanio, A.; Neri, R.; Tani, C.; Baldini, C.; Mosca, M.
Abstract : Background: Behçet's syndrome (BS) is a multisystemic, chronic relapsing inflammatory disease classified among the vasculitis. Eye involvement represent one of the most serious manifestation of BS and occurs in half of all patients. It seems more frequent and severe among young males and, unluckily, it still represents a significant cause of morbidity. Objectives: The aims of the study were: to study the relapse rate of BS patients with ocular involvement and to identify factors able to predict long-term outcome Methods: Among a cohort of 138 patients with a diagnosis of BS according the ISG criteria, 62 patients (37 males and 25 females; mean age at the onset 38±5 years) with ocular involvement were prospectively studied. The probability of clinical relapse after remission of the first ocular attack was calculated using the Kaplan-Meier method. Predictors of long-term outcome were identified by univariate analysis using the log-rank test and by multivariate analysis using Cox proportional hazards regression models. Results: The mean time between the first initial symptoms of BS and the onset of eye lesions was 2±2 years. The number of ocular attacks were the following: 43 posterior uveitis, 27 anterior uveitis, 26 retinal vasculitis, while panuveitis developed in 18 subjects. The cumulative relapse rates at 1 year, 3 years, and 5 years after remission of the first ocular attack were 41%, 31%, and 28%, respectively. On multivariate analysis, a younger age (<30 years) at the onset of ocular involvement, male sex and medical treatments other than biological agents represent independent predictive factors for more early relapses in BS patients with ocular involvement. Conclusions: The relapse rate seems to be more frequent in the first years of diseases, and probably it could be related to the fact the disease tend to grow dim over time. As literature data suggest, younger age and male sex still represent predictive factors of poor long-term clinical outcome. Disclosure of Interest: None declared